Novel components of germline sex determination acting downstream of foxl3 in medaka - Kikuchi, Mariko; Gutiérrez Triana, José Arturo; Mateo, Juan L.; Wittbrodt, Joachim (Developmental biology, 2019)
Germline sex determination is an essential process for the production of sexually dimorphic gametes. In medaka, Forkhead box L3 (foxl3) was previously identified as a germ cell-intrinsic regulator of sex determination that suppresses the initiation of spermatogenesis in female germ cells. To reveal the molecular mechanism of germline sex determination by foxl3, we conducted the following four analyses: Comparison of transcriptomes between wild-type and foxl3-mutant germ cells; epistatic analysis; identification of the FOXL3-binding motif; and ChIP-qPCR assay using a FOXL3-monoclonal antibody. We identified two candidate genes acting downstream of foxl3: Rec8a and fbxo47. It has been known that Rec8 regulates sister chromatid cohesion and Fbxo47 acts as a ubiquitin E3 ligase. These functions have not been, however, associated with sexual differentiation in germ cells. Our results uncover novel components acting downstream of foxl3, providing insights into the mechanism of germline sex determination.
Available online 27 October 2018
Gesehen am 06.08.2019